Dampak Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Pada Distributor Bahan Bangunan Di PT Vayata Senada Cemerlang - Putri Fadhillah; Ahmad Taufiq Harahap; Al Firah (Journal Economic Management and Business, 2026)
This study aims to determine and analyze the effect of service quality and price on customer satisfaction at the building materials distributor of PT Vayata Senada Cemerlang. Customer satisfaction is one of the important factors for companies in maintaining customers and increasing company competitiveness amid increasingly tight business competition. The research method used in this study is a quantitative method with descriptive and associative approaches. The population in this study consisted of all customers of PT Vayata Senada Cemerlang, with a sample of 83 respondents obtained through a questionnaire technique. The data analysis techniques used include validity test, reliability test, multiple linear regression analysis, t-test, F-test, and coefficient of determination using the SPSS program. The results of the study show that partially service quality has a positive but not significant effect on customer satisfaction, while price has a positive and significant effect on customer satisfaction. Simultaneously, service quality and price have a significant effect on customer satisfaction at PT Vayata Senada Cemerlang. This indicates that the better the service quality and the more appropriate the price offered, the higher the level of customer satisfaction will be. Based on these results, the company is expected to continuously improve service quality and set competitiveprices in order to increase customer satisfaction and maintain customer loyalty.